The association between GP organisational factors and the effectiveness of a prevention programme for cardiometabolic diseases: a prospective intervention study. Issue 5 (December 2020) - Badenbroek, Ilse F; Stol, Daphne M; Nielen, Markus MJ; Hollander, Monika; Wit, Niek J de; Schellevis, François G
No abstract available